ANALYSIS OF SUSTAINABLE DEVELOPMENT INDEX IN THE WEST SUMATERA (JURNAL ECONOMICA : Research of Economic And Economic Education, 2020)
With the end of the era of the Millennium Development Goals (MDGs), thoughts have arisen to re-search for internationally agreed development goals. Sustainable Development Goals (SDGs) are one of them. In this research, sustainable development is described as a balance of economic, social and environmental development. Sustainable development achievements are measured using a partial approach between indicators. The development indicators partially indicate progress in the economic and social fields. But progress in both fields seems to put pressure on the environment. The Sustainable Development Index (IPB), which is a composite of the GRDP, IPM and IKLH also gives the same message. By using multiple linear regression analysis, the results show that the human development index has the most influence on sustainable development in West Sumatra with a coefficient of 0.792.